Project-based learning in English academic writing: Students’ and lecturer’s views, hindrances, and practical strategies - Atmojo, Arief Eko Priyo; Hanifah, Zahrotun (UIN Raden Mas Said Surakarta, 2024)
Despite a plethora of studies on project-based learning (PjBL) for teaching English academic writing in a higher education setting, it has remained underinvestigated in non-English department contexts, and students’ practical strategies to overcome hindrances have also been underexplored. This present study scrutinizes the views, hindrances, and practical strategies involved in the enactment of PjBL for teaching English academic writing in a non-English department setting. This study adopted a qualitative research method with a single-case study design. Three undergraduate students and one English academic writing lecturer were purposefully recruited as participants. Data were gathered through individual, semi-structured interviews. Thematic analysis was utilized to analyze the data, and member checking was employed to ensure trustworthiness. The findings suggest that the students positively viewed the enactment of PjBL as very helpful although they had mixed opinions about whether the project should be carried out individually or in groups. Moreover, PjBL offers four advantages, including minimizing individual tasks, avoiding getting stuck, accomplishing the project in a well-planned manner, and engaging students more actively. Appropriate technological tools and teaching media are encouraged to be incorporated into PjBL. Although several hindrances related to teamwork and writing were encountered, the students attempted to overcome these hindrances with some practical strategies. Implications, limitations, and future studies are also discussed.